Radon in groundwaters from Guarany aquifer, South America: environmental and exploration implications - Bonotto, Daniel Marcos [UNESP]; Caprioglio, L. (Elsevier B.V., 2002)
Groundwater and sandstone samples were analyzed for radon in Guarany aquifer, Parana sedimentary basin, South America. The dissolved radon ranged between 3 and 3303 pCi/l, being lognormally distributed, with a modal value of 1315 pCi/l, and a median value of 330 pCi/l. Rn-222 leakage experiments for sandstones yielded a theoretical value of 1390 pCi/l for Rn-222 in water, showing that theoretical modeling can reliably be used to interpret laboratory and field data. (C) 2002 Elsevier B.V. Ltd. All rights reserved.
Keywords: radon; groundwater; Guarany aquifer; water-rock interaction